Trichomoniasis and associated factors in Rugarama hospital, a peri-urban health facility in south western Uganda - Tumuhaise, Dinavence; Akampurira, Nicholas; Nuwamanya, Neus; Ndulu, Mahela Ngunila; Mgelwa, Jonathan Paul; Benson, Okongo; Catherine, Abaasa; Muwanguzi, Enoch; Ampaire, Lucas; Rugera, Simon; Ssedyabane, Frank; Kalyetsi, Rogers (Journal of Protozoology Research, 2024)
Trichomoniasis is one of the neglected sexually transmitted infections caused by Trichomonas vaginalis. A cross-sectional study to determine the prevalence and factors associated with trichomoniasis among patients seeking medical services at Rugarama hospital, Uganda was done between February – March 2023. 150 study participants were recruited, and a semi-structured questionnaire was used to collect qualitative data. Vaginal and urethral swabs were collected aseptically, wet preparations were made for motility, and permanent slides were made, stained using the Giemsa staining technique and examined microscopically to identify Trichomonas vaginalis trophozoites morphologically. The data was analyzed using Excel and SPSS. A chi-square was used to determine variables related to trichomoniasis. Multivariate logistic regression was performed to determine factors associated with trichomoniasis. A p-value of less than 0.05 was considered statistically significant. The majority of the participants 78.7% (118/150) were female, had a primary level of education 55.3% (83/150), rural residence 65.3% (98/150), and married 55.3% (83/150). 6.7% (10/150) had trichomoniasis and were all female. Being married/ cohabiting (P- 0.022, 95% CI 0.067-8.350, OR 0.995) and cleaning private parts less than 3 days a week (P- 0.017, 95% CI 0.029-0.672, OR 0.0014) had a statistically significant association with trichomoniasis. The prevalence of trichomoniasis was 6.7%. Factors associated with the T. vaginalis infection were being married or cohabiting and cleaning the house less than 3 days a week. Routine screening for T. vaginalis is vital for early diagnosis and disease management. Health education and sensitization of the masses about personal hygiene, protected sex, and avoiding multiple sexual partners.
Keywords: Associated factors; Trichomonas vaginalis; Trichomoniasis; sexually transmitted disease; Uganda